2007
DOI: 10.4049/jimmunol.178.7.4424
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antibody Polyspecificity and Lipid Reactivity in Binding of Broadly Neutralizing Anti-HIV-1 Envelope Human Monoclonal Antibodies 2F5 and 4E10 to Glycoprotein 41 Membrane Proximal Envelope Epitopes

Abstract: Two neutralizing human mAbs, 2F5 and 4E10, that react with the HIV-1 envelope gp41 membrane proximal region are also polyspecific autoantibodies that bind to anionic phospholipids. To determine the autoantibody nature of these Abs, we have compared their reactivities with human anti-cardiolipin mAbs derived from a primary antiphospholipid syndrome patient. To define the role of lipid polyreactivity in binding of 2F5 and 4E10 mAbs to HIV-1 envelope membrane proximal epitopes, we determined the kinetics of bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
328
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(349 citation statements)
references
References 56 publications
19
328
1
1
Order By: Relevance
“…In some HIVinfected individuals, it is increased even more, to about 75% of the B cells that make mAbs that bind gp140, a prominent antigenic glycoprotein spike on the HIV-1 virus (53). Many of these mAbs, like the multireactive 2F5 and 4E10 mAbs from other HIV-infected individuals, also bind cardiolipin, a phospholipid in many cell membranes (32,33). The remarkably high frequency of these multireactive Abs, which have switched H chains and mutated V domains, suggests that they are selected by the HIV-1 virus, particularly during affinity maturation.…”
Section: Multispecificty Vs Monospecificitymentioning
confidence: 99%
See 1 more Smart Citation
“…In some HIVinfected individuals, it is increased even more, to about 75% of the B cells that make mAbs that bind gp140, a prominent antigenic glycoprotein spike on the HIV-1 virus (53). Many of these mAbs, like the multireactive 2F5 and 4E10 mAbs from other HIV-infected individuals, also bind cardiolipin, a phospholipid in many cell membranes (32,33). The remarkably high frequency of these multireactive Abs, which have switched H chains and mutated V domains, suggests that they are selected by the HIV-1 virus, particularly during affinity maturation.…”
Section: Multispecificty Vs Monospecificitymentioning
confidence: 99%
“…A mAb (7G12) raised against a porphyrin bound an unrelated polyether (31). Moreover, two mAbs (2F5 and 4E10) from HIV-infected individuals reacted with a viral protein (gp41) and also bound cardiolipin and other phospholipids (32,33). Yet another mAb (IgG1b12) from an HIV-infected person, in addition to binding the gp120 protein of the virus, reacted with dsDNA, histones, and "centromere B" (33).…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…Since the initial findings by Grunder et al and Ofek et al (12,22), a number of publications have also shown that 2F5, 4E10, and Z13e1 improve binding to Env and epitope peptides in a lipid environment (21,23,24). In addition, it has become increasingly clear that 4E10 binds to lipids in the absence of the MPER (21,(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In addition, it has become increasingly clear that 4E10 binds to lipids in the absence of the MPER (21,(23)(24)(25)(26)(27)(28)(29). These studies have generated models of 4E10 epitope recognition (21,23), but they have not yet fully addressed which antibody region(s) bind lipid and, of particular importance for vaccine design, whether lipid interaction is an essential component of MPER-mediated neutralization.…”
mentioning
confidence: 99%
“…V1V2 glycopeptide-binding K d and rate-constant measurements were carried out on BIAcore 3000 instruments (GE Healthcare) as described earlier (41,42). Anti-human IgG Fc antibody (Sigma Chemicals) was immobilized on either a CM3 or CM5 (CM3 for kinetics and K d determination) sensor chip (to minimize nonspecific binding of peptides to the chip matrix) to about 5,000 resonance units (RUs), and each antibody was captured to about 100-200 RU on individual flow cells in addition to one flow cell with the control Synagis mAb on the same sensor chip.…”
Section: Methodsmentioning
confidence: 99%